The methods used to translate medical terms between Arabic and Spanish: Los métodos utilizados para traducir términos médicos entre árabe y español (Journal of the College of Languages (JCL), 2021)
The present paper deals with medical terms translation and its relationship with the medical text of Arabic and Spanish. Medical translation is the process of transferring texts related to the field of health and medicine to achieve an accurate effective translation from the source language text to the equivalent target language text. The most prominent medical translations are from English to Arabic as most of the syllabuses in Arab countries are taught in English. Translation is an innovative work intended to render the original text in the source language into the target language with the highest level of linguistic and intellectual ability, through maintaining the utmost integrity of the text by using the core meaning present in the source text to create a new whole, namely, the target text. The present study object is to study and analyze medical texts of Arabic and Spanish according to medical translation. The study seeks solutions to medical term translation problems and corrects some of the translated medical terms errors. The study uses various dictionaries to analyze medical terms, including (DLE) dictionary, (AZ) medical dictionary and electronic dictionary (Reverso context).Through the analysis of the translated medical terms and its idiomatic body, the present study sheds light on the importance of the translated medical terms and the great role it plays in the development of medical science. The study’s main goal addresses the issues and the problems of the translation of medical texts into Arabic from all its related aspects. Resumen En este estudio, hemos presentado de traducir los términos médicos y su relación con el texto médico entre el árabe y el español. La traducción médica es el proceso de transferencia de textos relativos al campo de la salud y la medicina desde un idioma denominado " lenguaje de referencia " a los otros idiomas, conocido como idioma de destino, con la multiplicidad de tipos de idiomas de origen y destino, pero las traducciones médicas más destacadas son del inglés al árabe, al igual que la mayoría de los planes de estudios médicos en nuestros países árabes que se imparten en inglés.La traducción es un trabajo innovador, destinado a reformular el texto original con el alto nivel de habilidad lingüística e intelectual, manteniendo la máxima integridad para el texto, su espíritu y su contenido. Su objetivo es estudiar los textos médicos y analizarlos entre el árabe y el español sobre las bases en la traducción de textos, términos médicos y otros. Además, buscar soluciones a este problema del término médico. Mientras tanto, utilizaremos varios diccionarios para analizar términos, incluido el diccionario (DLE), el diccionario médico (AZ) y el diccionario electrónico (Reverso context), haremos un estudio analítico de estos términos médicos.También se corrigió lo incorrecto, revelando así la estructura del término extranjero y árabe y la idea de su nombre, la traducción fue la causa del desarrollo de la ciencia médica.En mi estudio de los términos médicos, he tratado absorber la fertilidad del cuerpo idiomático en beneficio de la traducción médica y de la lengua árabe, hemos presentado de este estudio de términos médicos, analizándolos y criticándolos. Nuestro interés en esta investigación ha sido abordar el tema de la traducción de textos médicos al lenguaje árabe y al problema de la transferencia del término médico, y hemos intentado contener este estudio en todos los aspectos relacionados.